Translation semantic variability: How semantic relatedness affects learning of translation-ambiguous words*. Issue 4 (31st March 2016) - BRACKEN, JENNIFER; DEGANI, TAMAR; EDDINGTON, CHELSEA; TOKOWICZ, NATASHA
Abstract : Translations often do not align directly across languages, and indirect mappings reduce the accuracy of language learning. To facilitate examination of this issue, we developed a new continuous measure for quantifying the semantic relatedness of words with more than one translation (hereafter translation-ambiguous words). Participants rated the similarity of each translation to every other translation, yielding a Translation Semantic Variability (TSV) score, ranging from 1.00 (unrelated) to 7.00 (related). Then, we determined how relatedness between translations affects translation-ambiguous word learning from German to English. German words with low TSV scores were recognized as translations more slowly and less accurately than German words with high TSV scores. TSV explains unique variance beyond the previously-used dichotomous classification of words as form vs. meaning ambiguous. We propose that the relatedness of the translation alternatives influences learning because it affects the ease with which a one-to-one mapping can be established between form and meaning.